2015
DOI: 10.1039/c4ra13893g
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of large-scale P3HT patterns by confined evaporation in the capillary tube

Abstract: A facile and robust route to fabricate large area patterns of poly(3-hexylthiophene) (P3HT) was developed by controlled evaporative self-assembly (CESA) technique within a confined space (capillary tubes). Properties of P3HT, solvents effects and inner surface properties of the capillary tube were systematically investigated.The results showed that the patterns could be controlled to evolve from dot deposits and stripes with fingering instabilities, to highly regular, nearly perfect stripes. The orientation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…In recent years, some alternative strategies that could more simply enable large-area ordered patterns using controlled evaporative self-assembly (CESA) have been reported. When a drying droplet is confined in space, evaporation is restricted to the edges, so that an outward capillary flow carries the solvent and solute from the interior to the contact line to compensate for the loss of the solvent, leaving behind a well-ordered patterned subject to the confined geometry. For instance, Lin et al demonstrated macroscopically well-organized gradient patterns of conjugated polymers such as poly­(3-butylthiophene) (P3BT), poly­(3-hexylthiophene) (P3HT), and P3BT- b -P3HT (P3BHT) by evaporating the corresponding polymer solutions in an axially symmetric cylinder on a Si substrate .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some alternative strategies that could more simply enable large-area ordered patterns using controlled evaporative self-assembly (CESA) have been reported. When a drying droplet is confined in space, evaporation is restricted to the edges, so that an outward capillary flow carries the solvent and solute from the interior to the contact line to compensate for the loss of the solvent, leaving behind a well-ordered patterned subject to the confined geometry. For instance, Lin et al demonstrated macroscopically well-organized gradient patterns of conjugated polymers such as poly­(3-butylthiophene) (P3BT), poly­(3-hexylthiophene) (P3HT), and P3BT- b -P3HT (P3BHT) by evaporating the corresponding polymer solutions in an axially symmetric cylinder on a Si substrate .…”
Section: Introductionmentioning
confidence: 99%
“…Besides the pure scientific interest to understand the mechanisms responsible for this effect, it can also be important in a variety of technological applications. Evaporative particle deposition is involved in processes such as the controlled evaporative self-assembly (CESA), [1][2][3][4] fabrication of DNA/RNA micro-arrays, 5,6 or more traditional ones including for instance printing and coating.…”
Section: Introductionmentioning
confidence: 99%
“…However, an excessively high concentration of P3HT (5.0 mg/mL) may obstruct the formation of the sharp crystal lines due to the increase in viscosity of the P3HT solution as the solvent evaporates (Supporting Information, Figure S17). 37 Increased viscosity induces P3HT coating of the substrate as well as a relatively blunt P3HT crystal line that decreases the height of line (Supporting Information, Figure S17a-iv,b-iv). The parameter study summarized in Figure 4c demonstrates the wide range of programmability for the interval, width, and height of solution processed organic crystals.…”
Section: Resultsmentioning
confidence: 99%